The Ideal Ionic Liquid Salt Bridge for Direct Determination of Gibbs Energies of Transfer of Single Ions, Part II: Evaluation of the Role of Ion Solvation and Ion Mobilities. (7th February 2018) - Ermantraut, Andreas; Radtke, Valentin; Gebel, Niklas; Himmel, Daniel; Koslowski, Thorsten; Leito, Ivo; Krossing, Ingo
Abstract: An important intermediate goal to evaluate our concept for the assumption‐free determination of single‐ion Gibbs transfer energies Δ tr G°(i, S1 →S2 ) is presented. We executed the crucial steps a) and b) of the methodology, described in Part I of this treatise, exemplarily for Ag + and Cl ‐ with S1 being water and S2 being acetonitrile. The experiments showed that virtually all parts of the liquid junction potentials (LJPs) at both ends of a salt bridge cancel, if the bridge electrolyte is an "ideal" ionic liquid, that is, one with nearly identical diffusion of anion and cation. This ideality holds for [N2225 ] + [NTf2 ] ‐ in the pure IL, but also in water and acetonitrile solution. Electromotive force measurements of solvation cells between S1 and S2 demonstrated Nernstian behavior for Ag + concentration cells and constant like cell potentials for solutions with five tested Ag + counterions.